Playing it safe - Weaver, Ashley (Weaver, Ashley. Electra McDonnell novel, 2023)
"The third in the Electra McDonnell series from Edgar-nominated author Ashley Weaver, Playing It Safe is a delightful World War II mystery filled with spies, murder, romance, and wit ..."--